Автомобильный цифровой измеритель уровня топлива - Сергиенко, Николай Егорович; Маренич, А. Н. (НТУ "ХПИ", 2007)
In this work made the research about the choice of the circuit and structure automobile measurement of a fuel level. The block diagram, working-algorithm of digital measurement of a fuel level and its design are submitted.
Keywords: современный автомобиль; резистивный датчик; поплавковый преобразователь; проволочный резистор; ультразвуковые датчики; емкостные датчики